Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.cya.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The integration of information technology in higher education: A study of faculty's attitude towards IT adoption in the teaching process

Abstract: It is a reality that advancement of Information Technology revolutionized the business practices and strategies of entire industries. The field of higher education is not an exception to this phenomenon. Colleges and universities around the world are investing considerable amount of money to create Information Technology resources that meet their student's and faculty's instructional needs. While universities encourage their faculties to adopt the new technologies for their preparation and delivery of classes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 46 publications
10
69
1
5
Order By: Relevance
“…Libraries that provide ICT (Information and Communication Technology) facilities and e-journal subscriptions are more attractive to students as a place to study and research (Brendan, Boniface, Ezema, & Ugwu, 2014) Technological acceptance in the form of ease of use e-learning system and infrastructure capability significantly influence the effectiveness of E-CRM (Jafari Navimipour & Soltani, 2016). The CRM model can improve the relationship between prospective customers (students, parents and communities) with institutions in creating emotional ties that can create two-way communication between users and providers of the academic system (Fathoni, 2014).The application of information technology significantly influences their ease and attitude towards the use of information technology education (John, 2015). Ease of use, access and reliability of the choice board system affect the satisfaction and decisions of system users (Bharati & Chaudhury, 2006).…”
mentioning
confidence: 99%
“…Libraries that provide ICT (Information and Communication Technology) facilities and e-journal subscriptions are more attractive to students as a place to study and research (Brendan, Boniface, Ezema, & Ugwu, 2014) Technological acceptance in the form of ease of use e-learning system and infrastructure capability significantly influence the effectiveness of E-CRM (Jafari Navimipour & Soltani, 2016). The CRM model can improve the relationship between prospective customers (students, parents and communities) with institutions in creating emotional ties that can create two-way communication between users and providers of the academic system (Fathoni, 2014).The application of information technology significantly influences their ease and attitude towards the use of information technology education (John, 2015). Ease of use, access and reliability of the choice board system affect the satisfaction and decisions of system users (Bharati & Chaudhury, 2006).…”
mentioning
confidence: 99%
“…HE institutions around the world are investing considerable amounts of money to create ICT resources that meet their students' and teachers' instructional needs (Ansyari, 2015;John, 2015;Watty, McKay, & Ngo, 2016). This is so because ICT is now integral to student learning experiences in most HE institutions.…”
Section: Discussionmentioning
confidence: 99%
“…It is noticed that ERP is gladly accepted by young staffs, which is showed by their eagerness to learn the software. Differences in acceptance to ERP also has been found among people with computer anxiety ) and experience of using computers (John, 2015). Those who have computer self-efficacy have been found to be accepting ERP gladly (John, 2015).…”
Section: People Factor Influencing Erp Success In Education Sectormentioning
confidence: 94%
“…Differences in acceptance to ERP also has been found among people with computer anxiety ) and experience of using computers (John, 2015). Those who have computer self-efficacy have been found to be accepting ERP gladly (John, 2015). Goel et al(2011) found that lack of knowledge related to ERP system was one factor which lead to failure in implementation.…”
Section: People Factor Influencing Erp Success In Education Sectormentioning
confidence: 99%